Le contrôle des armements et les armes chimiques - Vachon, G.K. (Études internationales, 1982)
Since the Soviet invasion of Afghanistan, the media has gone to great lengths to assess the relative capabilities of Warsaw Pact and NATO forces. Chemical weapons have not been neglected in these assessments, with the conclusion usually being that something should be done to match the capability of the Warsaw Pact to wage chemical warfare. In fact, important decisions have recently been made in the United States, and others are being considered elsewhere, which reflect that point of view.It is the position of this paper that the context within which chemical weapons have been considered in the past is too restrictive. Beginning with an examination of the role that chemical weapons are said to play in the East-West security framework, the article then goes on to a discussion of the global dimension of the issue. Finally, it outlines negociations underway to prohibit chemical weapons, and suggests that a regional approach to the problem might offer a way through the current impasse.